The anodic oxidation of calcium lactate : an estimation of the products of electrolysis and an investigation into some of the problems involved - Impey, Norman Robert Murray (Rhodes University, Faculty of Science, Department of Chemistry, 1949)
The subject of this thesis was chosen originally as a result of a suggestion made by a manufacturer of lactic acid. Lactic acid is made by a fermentation process from molasses and the acid is extracted from the fermentation liquors as calcium lactate. The conversion of the calcium lactate back to lactic acid is a tedious process from an industrial point of view. It was therefore suggested that the conversion may be more easily accomplished by electrolysis. The first experimental work was conducted with this object in view, but it soon became apparent that it was unlikely that lactic acid could be produced in suitable quantities for industrial purposes by this means. There was no reference in the literature to the electrolysis of calcium lactate, and little reference to the electrolysis of lactates in general, and what there was appeared to be conflicting, so it was decided to continue the investigation into the subject in order to determine what are the products of the anodic oxidation of calcium lactate. Intro., p.1.
Keywords: Electrolytic oxidation